Changes in mechanical properties of GFRP composite after exposure to warm seawater. (August 2017) - Ronagh, Hamid; Saeed, Nariman
This article presents the results of tensile tests performed on E-glass/Epoxy composite coupons. Eighteen GFRP panels were manufactured and cured in laboratory environment, out of which specimens in size of 25 mm × 250 mm specimens were cut. The specimens were categorised into three groups; the first group was post-cured at 60℃ oven for 16 h while the second and the third groups were placed under seawater at 60℃ for about 60 days and 4 months to represent saturation condition and ageing, respectively. The mechanical parameters such as elastic modulus (E), ultimate tensile strain (ɛu) and shear modulus (G) which are reported here were measured and were compared to one another showing that these are influenced by different conditioning regimes to a great extent.